Microalloyed steels. (20th April 2016) - Baker, T. N.
Abstract : This review considers the compositions, the main process routes, microstructure and structural properties of microalloyed steels. The background and brief history are followed by sections dealing with aspects of precipitation, which control grain size and dispersion strengthening in ferrite–pearlite steels, the approaches to modelling thermomechanical processing and the influence of multiple additions of transition metals on properties. High strength acicular ferrite/bainite steels used for linepipe are included and lead to super bainite steels. Around 12% of the world strip production is processed by the thin slab direct charging route, which is considered in some detail. The weldability of microalloyed steels now embraces joining using friction stir welding, which is discussed. Over the years, many approaches have been developed to predict the structural properties of these steels. They comprise several quantifiable microstructural features including possible atom clusters, relatively recently identified through atom probe tomography. A comprehensive collection of references is provided.